An MRI method for monitoring the ripening of Grana Padano cheese. (January 2016) - Mulas, G.; Anedda, R.; Longo, D.L.; Roggio, T.; Uzzau, S.
Abstract: In this paper, we propose a magnetic resonance imaging (MRI) method for assessing the ripening stage of Grana Padano, one of the most appreciated long-ripened hard cooked Italian cheeses. The method is based on a combination of MRI analysis with a study of multi-component transverse relaxation ( T 2 ) distributions. Three different ripening stages (12, 16 and 20 months) were considered and, for each stage, three samples were investigated (for a total of nine samples). The relaxation profiles of differently ripened Grana Padano cheeses varied in terms of area fraction relative to the three observed components of T 2 relaxation. In particular, a good linear relationship was observed between the area fraction of the first T 2 population (mainly constituted by water protons in chemical exchange with labile protein protons) and the months of ripening. The proposed method might have a general validity for different kinds of cheese.